Quality control in pile management system [electronic resource] - 226780 Teong, Lay Ming (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana Sains (Pengurusan Pembinaan)) - Universiti Teknologi Malaysia, 2007